Building a Website Using CMS Wordpress as a Media for Online SalesPromotion - Walidain, Fathurrahman; M Ripki Ade, Irawan; Pratama, Yusuf Hendra (Universitas Islam Al-Azhar Mataram, 2024)
In this digital era, websites have become an important tool for promoting business. One of the popular platforms for building websites is WordPress. WordPress is an open-source and easy-to-use Content Management System (CMS), so it is the choice of many people, including for promotional purposes. This research aims to analyze the effectiveness of using the WordPress CMS as a promotional medium in increasing brand awareness and sales. Di era digital ini, website menjadi salah satu alat penting untuk mempromosikan bisnis. Salah satu platform yang populer untuk membangun website adalah WordPress. WordPress adalah Content Management System (CMS) yang open-source dan mudah digunakan, sehingga menjadi pilihan banyak orang, termasuk untuk keperluan promosi. Penelitian ini bertujuan untuk menganalisis efektivitas penggunaan CMS WordPress sebagai media promosi dalam meningkatkan brand awareness dan penjualan.